2003
DOI: 10.1097/00004728-200309000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography of Partial Anomalous Pulmonary Venous Connection in Adults

Abstract: A partial anomalous pulmonary venous connection was seen in 0.2% of adults on CT. In contrast to previous series focusing on children, the anomalous vein in adults was most commonly from the left upper lobe, in women, and infrequently associated with atrial septal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 9 publications
3
83
1
2
Order By: Relevance
“…While previous studies corroborate this statement (Brody 1942;Snellen et al 1968), a more recent study examining the prevalence of partial anomalous pulmonary venous return using computed tomography provides conflicting data. In this study, 79% had an anomalous left upper lobe vein draining into a persistent left vertical vein, 17% had a right upper lobe vein draining into the superior vena cava, and 3% had a right lower lobe vein draining into the suprahepatic inferior vena cava (Haramati et al 2003). This difference in prevalence may partially be due to easier detection of left upper lobe anomalous veins than right upper lobe anomalous veins with computed tomography (Haramati et al 2003).…”
mentioning
confidence: 63%
“…While previous studies corroborate this statement (Brody 1942;Snellen et al 1968), a more recent study examining the prevalence of partial anomalous pulmonary venous return using computed tomography provides conflicting data. In this study, 79% had an anomalous left upper lobe vein draining into a persistent left vertical vein, 17% had a right upper lobe vein draining into the superior vena cava, and 3% had a right lower lobe vein draining into the suprahepatic inferior vena cava (Haramati et al 2003). This difference in prevalence may partially be due to easier detection of left upper lobe anomalous veins than right upper lobe anomalous veins with computed tomography (Haramati et al 2003).…”
mentioning
confidence: 63%
“…3) In contrast, a recent review of 29 cases of PAPVC incidentally found on CT in adults showed that 79% of PAPVC was located in the left upper lobe, and complication of ASD was very rare (3%). 4) In 7 previous case reports of PAPVC associated with lung cancer, 5 cases (63%) had anomalous vein in left upper lobe, and none of these cases had ASD ( Table 1). [5][6][7][8][9][10][11] These reports indicate that incidental adult PAPVC is most frequently found in the left upper lobe, and infrequently associated with ASD.…”
Section: Discussionmentioning
confidence: 85%
“…It is more easily diagnosed on the left side in comparison to the right. 4) On the left side, typically, a tubular structure is detected beside aortic arch in a location where only mediastinal fat normally exists. On the other hand, PAPVC is difficult to diagnose on echocardiography or chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…5 PAPVC is often clinically silent and recently in a retrospective review of computed tomography (CT) series in adults who had undergone imaging for other indications, have identified prevalence rates of 0.1e0.2% in the adult population. 6 Persistent anomalous pulmonary venous connection acts similar to a left-to-right shunt and over time (which may span between few years to decades), the increase in pulmonary blood flow can lead to progressive remodeling of the pulmonary vasculature which may cause increased pulmonary vascular resistance. If the remodeling and vasoconstriction of the pulmonary vasculature is severe enough, pulmonary arterial hypertension (PAH) and right ventricular pressure overload occur which may subsequently lead to RV failure.…”
Section: Discussionmentioning
confidence: 99%